Impact of exchange controls on South African public equity investment performance - Mathews, Marc John (My University, 2021)
The study investigates the impact of changes in regulation which allowed for South African investors to diversify equity portfolios internationally. Since 1995 exchange control regulations have been relaxed from completely prohibiting international equity investment to allowing up to 40% exposure for institutional investors. Since 2010, in effect no limits are seton the ability of an individual to diversify internationally. No previous study has considered the impact that structural barriers such as exchange control have had on the ability of South African investors to diversify internationally. The mean-variance spanning test was utilised to determine the scope for diversification benefits each time regulations changed and the magnitude of the benefit was measured as a change in the Sharpe ratio. Overall, the study found that the relaxation of regulations would have allowed for improved investment performance. However, regulatory restrictions limited some of the benefit for institutional investors while individual investors could have been able to benefit slightly more
A thesis submitted to the Wits Business School, Faculty of Commerce, Law and Management, at the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Finance and Investment), 2021
Keywords: Exchange control; South African public equity investment; Investors; International equity investment; SDG-8: Decent work and economic growth